Strategi Media Sosial Sebagai Pendorong Pertumbuhan Bisnis: Studi Kasus Shopee Indonesia - Maatuil, Rexy Andalangi; Noviyanto Tamatompo; Ferlita Aryanti Pusung; Marcelino Manolimay; Verdinan Liju (Indonesia Economic Journal, 2025)
Shopee Indonesia's social media strategy has proven effective in driving business growth in the competitive digital era. Shopee utilizes various social media platforms, such as Instagram, TikTok, YouTube, and Facebook, to reach a broad, heterogeneous, and active online audience. Each platform is utilized according to its user characteristics through creative, relevant, and interactive content, including sales promotions, thematic campaigns, live streaming, short entertainment, and strategic collaborations with influencers. This approach is not only oriented towards product offerings but also aims to build emotional closeness, trust, and user loyalty through two-way communication. The impact is reflected in increased brand awareness, engagement, frequency of interactions, and active user participation in various Shopee programs and features. Furthermore, consistent brand messaging, utilization of digital trends, and adaptation of platform algorithms further strengthen Shopee's position amidst intense e-commerce competition. Thus, social media strategy plays a significant role as a marketing tool, a means of communication, and a key driver of Shopee Indonesia's sustainable business growth.